An experimental study of lateral charge transfer in silicon nanocrystal layer embedded in SiO2 thin film - Wong, J. I. (2015)
Lateral charge transfer in a Si nanocrystal (nc-Si) layer embedded in a SiO2 thin film synthesized by Si ion implantation is investigated. When the nc-Si in one metal-oxide-semiconductor device is charged, the charging effect on both the charged device itself and the neighboring devices is monitored. With the existence of a continuous nc-Si layer in the spacing regions between the charged device and the neighboring devices, the charging operation induces a large flat-band voltage shift in the neighboring devices, and at the same time the charged device itself is also strongly affected in return. The phenomenon depends on both the nc-Si separation and the device spacing. It is attributed to the lateral charge transfer in the nc-Si layer. The result has an important indication for non-volatile memory applications of the nc-Si synthesized by the ion implantation technique.